Continuing Professional Development Training Related to the Use of Technology in Education in Saudi Universities: Literature Review - AlMutairi, Awatif; Alharbi, Omran; AlFaisal, Hailah Abdulaziz (Advances in Social Sciences Research Journal, 2022)
The CPD in regarding to E-Learning tools for educators and its role as an important element to develop and improve faculty members skills in adopting technology in education. As a result, the ministry of education in Saudi Arabia has made a huge effort to provide intensive training for educators in public schools and in universities. This paper aims to provide an overview of the CPD in Saudi education environment and presents its importance for improving educators’ skills’ especially, related to the adoption of technology in teaching and learning process. The results indicated that there were insufficient training courses for educators in related tot the integration of E-Learning strategies in education. The paper recommendations are that Saudi universities should provide adequate training which based on teachers’ requirements and needs.